The 1-2-3 Toolbox of Mainstream Economics: Promising Everything, Delivering Nothing - Shimshon Bichler; Jonathan Nitzan (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2021)
We write this essay for both lay readers and scientists, though mainstream economists are welcome to enjoy it too. Our subject is the basic toolbox of mainstream economics. The most important tools in this box are demand, supply and equilibrium. All mainstream economists – as well as many heterodox ones – use these tools, pretty much all the time. They are essential. Without them, the entire discipline collapses. But in our view, these are not scientific tools. Economists manipulate them on paper with impeccable success (at least in their own opinion). But the manipulations are entirely imaginary. Contrary to what economists tell us, demand, supply and equilibrium do not carry over to the actual world: they cannot be empirically identified; they cannot be observed, directly or indirectly; and they certainly cannot be objectively measured. And this is a problem because science without objective empirical tools is hardly science at all.
Keywords: E13; C01; O47; 330; demand; econometrics; equilibrium; neoclassical economics; science; supply